Perception, cognition, and decision training the quiet eye in action - Vickers, Joan N. 1945- (Human Kinetics, 2007)
"The book is organized into three parts. Part I introduces the visuomotor system and two processing systems that work together to permit the great range of actions humans perform. Eye-tracking technology is reviewed along with new possibilities for measuring what athletes really see when they perform. In part II, the author presents a unique framework of gaze control. Readers will learn how skilled athletes control the gaze to gain optimal control of their attention and decision making. The quiet eye phenomenon, measurement, and training are also addressed. Part III describes the three-step decision-training model and its application to how coaches design practice, provide feedback, use questions, and give instructions. Case studies show how others are using the model and the seven decision-training tools."--Pub. desc